Association of PARP1 polymorphisms with response to chemotherapy in patients with high‐risk neuroblastoma. Issue 7 (27th February 2020) - Avitabile, Marianna; Lasorsa, Vito Alessandro; Cantalupo, Sueva; Cardinale, Antonella; Cimmino, Flora; Montella, Annalaura; Capasso, Dalila; Haupt, Riccardo; Amoroso, Loredana; Garaventa, Alberto; Quattrone, Alessandro; Corrias, Maria Valeria; et al.
Abstract: The genetic aetiology and the molecular mechanisms that characterize high‐risk neuroblastoma are still little understood. The majority of high‐risk neuroblastoma patients do not take advantage of current induction therapy. So far, one of the main reasons liable for cancer therapeutic failure is the acquisition of resistance to cytotoxic anticancer drugs, because of the DNA repair system of tumour cells. PARP1 is one of the main DNA damage sensors involved in the DNA repair system and genomic stability. We observed that high PARP1 mRNA level is associated with unfavourable prognosis in 3 public gene expression NB patients' datasets and in 20 neuroblastomas analysed by qRT‐PCR. Among 4983 SNPs in PARP1, we selected two potential functional SNPs. We investigated the association of rs907187, in PARP1 promoter, and rs2048426 in non‐coding region with response chemotherapy in 121 Italian patients with high‐risk NB. Results showed that minor G allele of rs907187 associated with induction response of patients ( P = .02) and with decrease PARP1 mRNA levels in NB cell line ( P = .003). Furthermore, rs907187 was predicted to alter the binding site of E2F1 transcription factor. Specifically, allele G had low binding affinity with E2F1 whose expression positively correlates with PARP1 expression and associated with poor prognosis of patients with NB. By contrast, we did not find genetic association for the SNP rs2048426. These data reveal rs907187 as a novel potential risk variant associated with the failure of induction therapy for high‐risk NB.